2020
DOI: 10.1177/1748895820937401
|View full text |Cite
|
Sign up to set email alerts
|

Sexual deviance in prison: Queering identity and intimacy in prison research

Abstract: Recent years have seen increased attention in both research and policy towards lesbian, gay, bisexual and transgender prisoners as a group with distinct needs. This has been driven by wider political recognition of lesbian, gay, bisexual and transgender rights and research suggesting that lesbian, gay, bisexual and transgender prisoners are particularly ‘vulnerable’ to bullying and abuse within prison settings. Much of this research, and the policy solutions associated with it, we argue, ignores or si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Sykes (1958) claimed that the core “pains of imprisonment” that is, the loss of freedom, lack of supplies (e.g., hygiene supplies, foods, medicines), deprivation of (heterosexual) romantic relationships, and the isolation from outside community can have a strong impact on how offenders behave in correctional institutions. Studies found lack of supplies increased risk of theft-related bullying (Guo et al, 2019; Hassan et al, 2020), and sexual deprivation can be linked to sexual bullying in correctional institutions (Banbury et al, 2016; Carr et al, 2020) . Researchers agreed that some features of the institution generate enormous pressure that may increase the risk of bullying or other forms of aggressive behavior (Adams & Ireland, 2017; Ireland et al, 2016; Sekol et al, 2021), but not limited to these five Sykes’s deprivations.…”
Section: Theoretical Explanations Of Bullying Perpetrationmentioning
confidence: 99%
“…Sykes (1958) claimed that the core “pains of imprisonment” that is, the loss of freedom, lack of supplies (e.g., hygiene supplies, foods, medicines), deprivation of (heterosexual) romantic relationships, and the isolation from outside community can have a strong impact on how offenders behave in correctional institutions. Studies found lack of supplies increased risk of theft-related bullying (Guo et al, 2019; Hassan et al, 2020), and sexual deprivation can be linked to sexual bullying in correctional institutions (Banbury et al, 2016; Carr et al, 2020) . Researchers agreed that some features of the institution generate enormous pressure that may increase the risk of bullying or other forms of aggressive behavior (Adams & Ireland, 2017; Ireland et al, 2016; Sekol et al, 2021), but not limited to these five Sykes’s deprivations.…”
Section: Theoretical Explanations Of Bullying Perpetrationmentioning
confidence: 99%
“…Previous research has identified reduced feelings of safety as one of the potential negative effects of cell-sharing, and feeling unsafe in prison is associated with a lower quality of life, psychological distress and suicide ideation (for example, Favril et al, 2017; Liebling et al, 2005; Moran et al, 2013). Sexuality may be important to consider because individuals reporting a non-heterosexual identity may experience increased awkwardness with cellmates, as well as increased vulnerability to discrimination, potentially affecting their wellbeing (Carr et al, 2020; Dunn, 2013). Time served may also influence cell-sharing and wellbeing: individuals can often initially struggle to cope with the prison regime and rules in prison before then adapting as time progresses (Zamble and Porporino, 1988).…”
Section: Other Factors Influencing Cell-sharing and Wellbeing In Prisonmentioning
confidence: 99%
“…Besides that, other studies mention as stated in Ref. [21][22][23] these lesbians in general manner undetected so that notes about behavior of the lesbians only will can obtained when done examination by an experienced psychiatrist.…”
mentioning
confidence: 96%